CyberAlumni a Cybersecurity Collaboratory (Journal of The Colloquium for Information Systems Security Education, 2023)
CyberAlumni is a case study of a new model for using peer to peer digital networks to make students breach ready. The CyberAlumni organization was founded in 2021 with the goals of pursuing continuing education and collaborations with academia, industry, and government to bridge the gap between curriculum and job placement. This model serves to accelerate the professional development and acquisition of top-level cybersecurity talent while recursively bolstering cybersecurity curriculum in the process. All goals were achieved within one year, leading to further investigation of applying this model at scale in conjunction with courses offered through NSA Centers of Academic Excellence.
Keywords: Collaboratory; Scalability; Game-based Learning; NCAE-C; Non-traditional Students; Project-based Learning; Online and Remote Learning